Cadre-Led Sanitation Counseling and Maternal Stunting-Prevention Practices in Sigi Regency, Indonesia: A Cross-Sectional Study - Dedi Mahyudin Syam; Andi Bungawati; Udin Udin (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Stunting remains a major public health problem in Indonesia, particularly in high-burden areas such as Sigi Regency, Central Sulawesi. Poor sanitation and hygiene practices contribute to environmental enteric dysfunction (EED), which may impair nutrient absorption and child growth. Indonesia’s Community-Based Total Sanitation (STBM) program promotes sanitation-related behavior change through cadre-led interventions across five sanitation pillars. Methods: A cross-sectional design was used involving 80 mothers of stunted children under two years old, selected through proportional stratified random sampling across high-burden villages. Data were collected using a structured and validated 25-item questionnaire measuring behaviors aligned with the five STBM pillars. A score of ?75 (?75% of the maximum score) was categorized as